Learning together: Experimental evidence on the impact of group-based nutrition interventions in rural Bihar - Raghunathan, Kalyani; Kumar, Neha; Gupta, Shivani; Chauhan, Tarana; Kathuria, Ashi; Menon, Purnima (International Food Policy Research Institute, 2020)
Despite improvements over the last decade or more, India still accounts for a large proportion of the global prevalence of maternal and child undernutrition. We use a cluster-randomized controlled design and two waves of panel data on more than 2000 households from Bihar to analyse the impact on diet quality and anthropometry of a health and nutrition intervention delivered through an at-scale women’s self-help group (SHGs) platform. We find that the intervention had small but significant impacts on women and children’s dietary diversity, with the main impacts coming from an increase in the consumption of fruits and vegetables and dairy, however, it had no impact on women’s body mass index. We identify several potential pathways to impact. To the extent that SHGs can effect broad-based social change, their current reach to millions of women makes them a powerful platform for accelerating improvements in maternal and child health and nutrition outcomes.